Penerapan Prinsip Good Governance Dalam Pelayanan Administrasi di Kantor Desa Toto Utara Kabupaten Bone Bolango - Zakaria, Atika; Mozin, Sriyulianty; Nani, Yacip Noho (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The aim of this research is to determine the application of Good Governance principles in administrative services at the North Toto Village Office, Bone Bolango Regency. This research method is qualitative. Data collection techniques are interviews, observation and documentation techniques. Data analysis techniques through data reduction, data display and drawing conclusions. The results of the research show that the application of Good Governance principles in administrative services at the North Toto Village Office, Bone Bolango Regency has gone well but is not yet optimal. This is proven by administrative services that fulfill the principles of transparency, responsiveness, participation, fairness and accountability. However, the principles of efficiency and effectiveness are not yet optimal, this can be seen from the achievement of performance which is not in accordance with the target.